Implementation of the CIPPO Evaluation Model in Culinary Training - Anifah Widya Indarthi; Fakhruddin Fakhruddin; Mintarsih Arbarini; Rendi Agung Febrianto; Samira Agoro (Universitas Negeri Semarang, 2025)
Training in Indonesia has undergone industry- and curriculum-focused reforms. The government built BLKs in the regions to align training with industry needs. However, at BLK Pemalang Regency, there is a lack of human resources for training needs analysis, a limited number of instructors, manual administration of attendance records, and a lack of long-term evaluation of graduates. This study aims to analyze the implementation of the CIPPO evaluation model in culinary training. The research used a descriptive qualitative method. Data collection involved observation techniques, interviews with the organizing committee, trainees, and instructors, and documentation. Data validity was ensured through the triangulation of sources and methods. The data analysis technique adopted the Miles & Huberman technique, consisting of data collection, data reduction, data presentation, and conclusion. The research results showed that BLK has a legal basis and a supporting vision-mission, competent human resources, adequate facilities, and a systematic training process by the existing legal basis in improving participants' skills. However, in the outcome component, there is no post-training support and job placement facilities, which causes graduates to be independent in finding jobs, and there is no comprehensive evaluation of the absorption of graduates. It was concluded that there were improvements in participants' knowledge, attitudes, and skills, but BLK needs to strengthen post-training guidance and mentoring programs, improve administration with online systems, and make greater use of social media. This research reflects progress in evaluating culinary training at BLK Pemalang through the CIPPO model, which evaluates program outcomes and long-term benefits for graduates.